Retinal Complications After Lateral Rectus Transpositional Squint Surgeries: A Review of Literature - Prashant Kumar; Nasiq Hasan (Asian Journal of Medical Research, 2021)
In oculomotor nerve palsy, four of the ocular muscles is affected and the eye is in hypotropia and abducted position. The goal of the squint surgery is to bring the eye in primary position. Supramaximal recesession resection have been tried but of limited benefit. Transpositional squint surgeries have been described for the same to bring the eye in orthophoric position. These surgeries have been in practice since 1989 when it was first described by Taylor et al. Later on several modifications of this surgery was done by Kaufman et al (1992), Morad et al (2000), Graf M et al (2010), Abbas et al (2010), Gokyigit b et al(2013), Erbagci et al (2016) and Saxena et al (2016). Here we reviewed all the reported cases of lateral rectus transpositional squint surgeries done between 1989 and 2021, the reported retinal complications, their explanation and resolution. Pubmed library was used as a database.